2020
DOI: 10.1007/s00436-020-06895-x
|View full text |Cite
|
Sign up to set email alerts
|

Nest-type associated microclimatic conditions as potential drivers of ectoparasite infestations in African penguin nests

Abstract: Nest design and characteristics can influence the microclimatic conditions in the nest. Nest-dwelling ectoparasites are sensitive to temperature and moisture and as such the conditions in the nest can influence parasite infestations. The endangered African penguin (Spheniscus demersus) breeds in different nest types and as yet little is known with regard to the microclimate and parasite infestation within these nests. This study characterized the microclimatic conditions in natural open, natural covered (with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 75 publications
(108 reference statements)
0
13
0
Order By: Relevance
“…2007; Sherley et al . 2012; Pichegru 2013; Espinaze et al 2020) and Lei et al (2014) recommended the use of cement nests, which at the time showed higher breeding success than surface nests or fibreglass artificial nests in African Penguins breeding on Bird Island. However, these cement nests still posed a threat to penguins because of the high temperatures that they reached (above 50°C on occasions).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2007; Sherley et al . 2012; Pichegru 2013; Espinaze et al 2020) and Lei et al (2014) recommended the use of cement nests, which at the time showed higher breeding success than surface nests or fibreglass artificial nests in African Penguins breeding on Bird Island. However, these cement nests still posed a threat to penguins because of the high temperatures that they reached (above 50°C on occasions).…”
Section: Discussionmentioning
confidence: 99%
“…As part of this plan, managing authorities intervened by installing artificial nests at various breeding sites to protect penguins from extreme weather events and predation (Pichegru 2013). Several versions of these artificial nests have been tried with variable success (Kemper et al 2007;Sherley et al 2012;Pichegru 2013;Espinaze et al 2020) and Lei et al (2014) recommended the use of cement nests, which at the time showed higher breeding success than surface nests or fibreglass artificial nests in African Penguins breeding on Bird Island. However, these cement nests still posed a threat to penguins because of the high temperatures that they reached (above 50°C on occasions).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations